International commitment, post-entry growth and survival of international new ventures - Sleuwaegen, Leo; Onkelinx, Jonas (Journal of Business Venturing, 2014)
This paper makes several contributions to the emerging literature on the post-entry behavior of international new ventures. Based on an extensive longitudinal data set, we investigate the dynamics of commitment, growth and survival of different types of newly internationalizing Belgian firms. Global start-ups have the highest initial and rapidly rising export commitment per market and are also more likely to continue exporting over time than geographically focused start-ups, and traditional staged exporters. However, global start-ups also display the highest failure rate. This high failure rate appears to result primarily from the ‘liability of newness’ and less from the added complexity associated with rapid and wide scope internationalization.